The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/vbz.2014.1731
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey of Orthopoxvirus Infection Among Rodents in Hungary

Abstract: As a result of discontinuing vaccination against smallpox after the late 1970s, different orthopoxviruses (OPVs), such as cowpox virus (CPXV), have become a re-emerging healthcare threat among zoonotic pathogens. In Hungary, data on OPV prevalence among its rodent host species have been absent. Here, rodents belonging to four species, i.e., striped field mouse (Apodemus agrarius), yellow-necked mouse (A. flavicollis), wood mouse (A. sylvaticus) and bank vole (Myodes glareolus), were live trapped at 13 sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In Thuringia, they were striped field mice and in Saxony-Anhalt they were bank voles. In accordance to detailed investigations on wild rodents [ 17 , 20 , 21 , 22 , 41 ], these two species are identified as putative reservoir hosts for CPXV in nature. It remains unclear why none of the trapped rodents at the other two herds (Saxony and Brandenburg) were found seropositive for CPXV-specific antibodies.…”
Section: Discussionmentioning
confidence: 55%
“…In Thuringia, they were striped field mice and in Saxony-Anhalt they were bank voles. In accordance to detailed investigations on wild rodents [ 17 , 20 , 21 , 22 , 41 ], these two species are identified as putative reservoir hosts for CPXV in nature. It remains unclear why none of the trapped rodents at the other two herds (Saxony and Brandenburg) were found seropositive for CPXV-specific antibodies.…”
Section: Discussionmentioning
confidence: 55%
“…Consequently, in order to obtain virus isolates originating from reservoir host species, common voles should be sampled in Central Europe, while bank voles/field voles and wood mice are species to be sampled in UK and Fennoscandia, respectively. Seroprevalence and molecular survey data indicate CPXV infections are also occurring in bank voles in Central Europe (Belgium [ 19 ], Hungary [ 27 ]; Kinnunen 2011; our unpuplished data). However, these studies categorized sera as “positive” if titers were 1:20 or higher and could be the result of inefficient replication without efficient transmission.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that wild rodents are the reservoir hosts for CPXV [ 10 , 11 , 28 ], and we recently demonstrated the susceptibility of common voles for CPXV by experimental infection [ 33 ]. However, bank voles evidently are also affected as shown by serological and molecular surveys in Eurasia [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 26 , 27 ]. In addition, recent PCR investigations indicated CPXV infections in bank voles mainly of the Western lineage, but also in a single animal of the Eastern lineage ([ 21 ]; Fischer, Drewes, Ulrich et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations